Competency management and the financial results of the foreign subsidiaries of Polish MNCs: The empirical research findings - Stor, Marzena; Haromszeki, Łukasz (Human systems management, 2022)
BACKGROUND: Competency management (CM) is one of the basic subfunctions of HRM, which can significantly affect the results achieved by organizations. This is because the competencies of employees have become the key capital of enterprises and a factor of their success. Research on the relationships between CM and organizational performance results in Polish MNCs creates a research gap due to the object and subject of research. OBJECTIVE: The main goal of the article is to identify the potential regularities that may exist between the advancement level of CM and its composing activities and the company financial performance results. Of particular interest are the relationships that may appear between the studied variables in the context of their relationships with other subfunctions of HRM and the significance of human capital as a competitive factor. METHODS: The research sample includes 200 non-financial business entities with Polish capital, whose headquarters are in Poland, and local subsidiaries are located outside the country. The research was conducted using CATI and CAWI methods. Descriptive and correlation statistics were used to analyze the collected empirical data. RESULTS: Two fundamental regularities are observable. It turns out that the higher the advancement level of activities within CM, and in particular its links with other HRM subfunctions, the better the financial results of enterprises. CONCLUSIONS: The empirical research results lead to the conclusion that human capital is treated as a company’s competitive factor, and CM is of significant meaning to the financial results of the organization.